Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b ) 5x + x = 39 - 32
=> 6x = 39 - 9
6x = 30
x = 30 : 6
x = 5
a ) 5x + 3x = 36 : 32 . 4 + 12
=> 8x = 36-2 . 4 + 12
8x = 34 . 4 + 12
8x = 81 . 4 + 12
8x = 324 + 12
8x = 336
x = 336 : 8
x = 42
k nha !
1) 8x = 81 x 4 + 12
8x = 324 + 12
8x = 336
x = 336 : 8
x = 42
2) 6x = 30
x = 30 : 6
x = 5
nha ^^
a . 3x+(-24)= -9-(2x)
= 3x+(-24) = -9 +( -2x)
= 3x + 2x = -9 + 24
= 5x = 15
x = 15 : 5
x = 3
b .80+(5x)=9+(-20)
= 80 + 5x = -11
5x = -11 - 80
5x = -91
x = -91 : 5
x = -18,2 = \(\dfrac{-91}{5}\)
x
a) Ta có: \(18-x=58-\left(-30\right)\)
\(\Leftrightarrow18-x=88\)
\(\Leftrightarrow x=18-88=-70\)
Vậy: x=-70
b) Ta có: \(x-27=\left(-43\right)-9\)
\(\Leftrightarrow x-27=-43-9\)
\(\Leftrightarrow x-27=-52\)
\(\Leftrightarrow x=-25\)
Vậy: x=-25
c) Ta có: \(169-\left(x+4\right)=69\)
\(\Leftrightarrow x+4=169-69\)
\(\Leftrightarrow x+4=100\)
\(\Leftrightarrow x=96\)
Vậy: x=96
d) Ta có: \(\left(5x+3\right)-\left(-24+4\right)=33\)
\(\Leftrightarrow5x+3+24-4-33=0\)
\(\Leftrightarrow5x-10=0\)
\(\Leftrightarrow5x=10\)
\(\Leftrightarrow x=2\)
Vậy: x=2
e) Ta có: \(225-\frac{\left(5x+10\right)}{25}+5=-\left(-20\right)\)
\(\Leftrightarrow225-\frac{5x+10}{25}+5-20=0\)
⇔\(-\frac{5x+10}{25}+210=0\)
\(\Leftrightarrow-\frac{5x+10}{25}=-210\)
⇔\(\frac{5x+10}{25}=210\)
\(\Leftrightarrow5x+10=210\cdot25=5250\)
\(\Leftrightarrow5x=5250-10=5240\)
\(\Leftrightarrow x=1048\)
Vậy: x=1048
a) 7x - 5 = 16 b) 156 - 2x = 82 c) 10x + 65 = 125
=> 7x = 16 + 5 => 2x = 156 - 82 => 10x = 125 - 65
=> 7x = 21 => 2x = 74 => 10x = 60
=> x = 21 : 7 => x = 74 : 2 => x = 60 : 10
=> x = 3 => x = 37 => x = 6
Vậy x = 3 Vậy x = 37 Vậy x = 6
d) 8x + 2x = 25.2 e) 15 + 5x = 40 f) 5x + 2x = 6 - 5
=> 10x = 50 => 5x = 40 - 15 => 7x = 1
=> x = 50 : 10 => 5x = 25 => x = 1 : 7
=> x = 5 => x = 25 : 5 => x = 1/7
Vậy x = 5 => x = 5 Vậy x = 1/7
Vậy x = 5
g) 5x + x = 150 : 2 + 3 h) 6x + 3x = 5 : 5 + 3 i) 5x + 3x = 3 : 3 . 4 + 12
=> 6x = 75 + 3 => 9x = 1 + 3 => 8x = 1 . 4 + 12
=> 6x = 78 => 9x = 4 => 8x = 4 + 12
=> x = 78 : 6 => x = 4 : 9 => 8x = 16
=> x = 13 => x = 4/9 => x = 16 : 8
Vậy x = 13 Vậy x = 4/9 => x = 2
Vậy x = 2
j) 4x + 2x = 68 - 2 : 2 k) 5x + x = 39 - 3 : 3 l) 7x - x = 5 : 5 + 3 . 2 - 7
=> 6x = 68 - 1 => 6x = 39 - 1 => 6x = 1 + 6 - 7
=> 6x = 67 => 6x = 38 => 6x = 7 - 7
=> x = 67 : 6 => x = 38 : 6 => 6x = 0
=> x = 67/6 => x = 19/3 => x = 0
Vậy x = 67/6 Vậy x = 19/3 Vậy x = 0
m) 7x - 2x = 6 : 6 + 44 : 11
=> 5x = 1 + 4
=> 5x = 5
=> x = 5 : 5
=> x = 1
Vậy x = 1
Mỏi tay ~~~~~~~~~~~~~~
a, \(\left(x-158\right):6=20\)
\(x-158=20.6\)
\(x-158=120\)
\(x=120+158\)
\(x=278\)
~~~Hok tốt~~~
a) \(\left(x-158\right):6=20\)
\(\Leftrightarrow x-158=\frac{20}{6}=\frac{10}{3}\)
\(\Leftrightarrow x=\frac{10}{3}+158\)
\(\Leftrightarrow x=\frac{484}{3}\)
Vậy : \(x=\frac{484}{3}\)
b) \(x-1,25.4=2,5\)
\(\Leftrightarrow x-5=2,5\)
\(\Leftrightarrow x=2,5+5\)
\(\Leftrightarrow x=7,5\)
Vậy : \(x=7,5\)
c) \(x+0,25=\frac{43}{4}-\frac{18}{5}\)
\(\Leftrightarrow x+\frac{1}{4}=\frac{143}{20}\)
\(\Leftrightarrow x=\frac{143}{20}-\frac{1}{4}\)
\(\Leftrightarrow x=\frac{69}{10}\)
Vậy : \(x=\frac{69}{10}\)
a)5x(-20)
=(-100)
b)(-9)x4
=(-36)
t tôi nhé bn